Activity of subjects of authority in the field of aviation security - Гусар, Ольга Анатоліївна; Маслов, Феодосій Хассанович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
In the article features of activity of subjects of imperious powers in sphere of aviation safety are considered. An understanding of such a subject is formulated. The characteristic of their status characteristics is highlighted. Three structural levels in their system are proposed. The content of the competence of the subjects of authority in the field of aviation security is disclosed. The competence of civil aviation subjects in the field of aviation security and identifies integrative features that unite them into a systemic education were considered in the article. The essence of the activity of subjects of power in the field of aviation security is determined by their administrative and legal status. This status is characterized by competence, that is, rights, duties and subjects of conduct, and the legal personality of each of the min this sphere. The analysis of status characteristics of subjects of authority in the field of airtransport security makes it possible to distinguish three structural levels in their system. The first is the level of the Ministry of Infrastructure. At the second level is situated the State Aviation Service of Ukraine, the central executive authority authorized to operate in the field of civil aviation. The third level is the level of local executive bodies authorized for activities in the field of civilaviation. The activities of each of the subjects are carried out in accordance with the functions that are defined by special regulatory acts to ensure safety in civil aviation.